Bilateral investment treaties and foreign direct investment inflows: Evidence from an emerging economy - Giang, Mai, Huong; Nhu, Truong, Ngoc Cung; Trung, Bui, Huy (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of Bilateral Investment Treaties (BITs) on Foreign Direct Investment (FDI) inflows to Vietnam using a panel dataset of 36 partner countries from 2007 to 2019. Employing the Gravity Model, the analysis incorporates key determinants of FDI, including economic size, geographical distance, trade openness, macroeconomic stability, infrastructure, and institutional quality. The findings confirm that BITs play a significant role in attracting FDI, as they reduce investment risks and enhance investor confidence. The results also reveal that larger economies attract more FDI, while greater geographical distance deters investment. ASEAN membership and trade openness positively influence FDI, whereas inflation volatility and exchange rate fluctuations deter investment. Additionally, strong digital infrastructure and telecommunications contribute to greater FDI attractiveness. Among institutional factors, government effectiveness, the rule of law, and corruption control emerge as critical drivers of investor confidence. The study concludes that BITs are a useful tool to attract FDI, but their effectiveness is contingent upon complementary reforms and sound economic fundamentals. These findings offer practical implications for policymakers by emphasizing the importance of not only signing BITs but also improving domestic institutions and infrastructure to fully realize the benefits of international investment agreements.